Medication Adherence Interventions for Cardiovascular Disease in Low- and Middle-Income Countries: A Systematic Review - Ogungbe, Oluwabunmi (Patient Prefer Adherence, 2021)
PURPOSE: The burden of cardiovascular diseases (CVD) is high in low- and middle-income countries (LMICs). Medications are integral to the management and control of CVD; however, suboptimal adherence impacts health outcomes. This systematic review aims to critically examine interventions targeted at improving medication adherence among persons with CVD in LMICs. METHODS: In this systematic review, we searched online databases PubMed, Embase, and CINAHL for studies that evaluated a medication adherence intervention for CVD, reported adherence as an outcome measure, were conducted in LMICs and reported the strategy or tool used to measure adherence. We included articles published in English, available in full text, peer-reviewed, and published between 2010 and 2020. RESULTS: We included 45 articles in this review. The majority of the studies implemented counseling and educational interventions led by nurses, pharmacists, or community health workers. Many of the studies delivered medication-taking reminders in the form of phone calls, text messages, short message services (SMS), and in-phone calendars. Multi-component interventions were more effective than unifocal interventions. Interventions involving technology, such as mobile phone calls, electronic pillboxes, and interactive phone SMS reminders, were more effective than generic reminders. The outcomes reported in the studies varied based on the complexity and combination of strategies. When interventions were implemented at both the patient level, such as reminders, and at the provider level, such as team-based care, the effect on medication adherence was larger. CONCLUSION: In LMICs, medication adherence interventions among persons with CVD included a combination of patient education, reminders, fixed-dose combination therapy and team-based care approach were generally more effective than singular interventions. Among patients who had CVD, the medication adherence interventions were found to be moderately effective. Future studies focusing on improving medication adherence in LMICs should consider non-physician-led interventions and appropriately adapt the interventions to the local context.